(untitled) (Proceeding of the International Conference on Arts and Humanities, 2022)
This study examines COVID-19 as a public health problem in Nigeria as reflected in health issues raised about the disease in a SceneOne TV YouTube channel drama series Jenifa on Lockdown. The drama showcases the Nigerian experience of the first wave of COVID-19 in 2020. This study does a socio-pragmatic reading of highlighted health concerns from a stylistic perspective. It seeks to validate the applicability of utterances of characters to the establishment of the realness of COVID-19 and corruption as the bane of preventive and control measures in Nigeria. This research adopted a qualitative approach. It employed John Searles’ model of Speech Act Theory as its theoretical framework. Relevant illocutionary acts were collected from selected episodes of the satirical performance as data. The paper reveals that COVID-19 is a major public health problem in Nigeria. It identifies political corruption, especially the embezzlement of budgetary allocation to health as a factor that undermines the implementation of a desired high-level strategic response to the disease. It distinguishes health challenges such as underfunding and understaffing of the health sector, alarming population per health center, lack of isolation centers, non-remuneration of frontline health workers, unethical practices among health workers, and the discouragement of volunteerism as consequences. It concludes that ridding Nigeria of corruption is necessary to solve identified health challenges and improve its health care system. It recommends a bottom-top approach that entails social accountability to achieve answerability, good governance, a successful and sustainable health system in Nigeria. This research endorses the effectiveness of dramatic campaigns on social media in health promotion. It establishes the efficiency of the approach to health care and wellbeing, using insights from dramatic performance, stylistics, and pragmatics. Thus, it suggests further linguistic research into critical, dramatic perceptions of health to boost healthcare and wellbeing.